Analisis Kinerja DPRD Kabupaten Bungo dalam Menampung Aspirasi Masyarakat pada Periode 2014-2019 - Maros, Asra'i (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2018)
Shelter aspirations of the people is an obligation for every member of the board of the ordinary and routine executed by board members during session breaks to meet their constituents, and this activity is known as the recess. Objective is to describe the performance of Bungo Regency period 2014-2019 for shelter aspirations of the people and to analyze the factors supporting and inhibiting performance Bungo Regency period 2014-2019 for shelter aspirations of the people. Measuring the performance of parliaments in holding aspirations of the people rated of the three indicators of accountability, responsiveness and effectiveness. The method used is descriptive qualitative. The results showed performance Bungo Regency period 2014-2019 in accommodating the aspirations of the people who carried on the recess is not maximized implemented, can be seen from the level of accountability is still low due to the overall aspirations of the community yet Bungo successfully accommodated by board members. Responsiveness is also low because the institutions have not been able to respond to the needs of the board and creating a development which according to community needs. And the effectiveness is still low, due to the quantity recess has not been implemented three times in one year and has not 100% member of the board agenda recess as well as the quality has not been effective because it has not the appropriate procedure. Factors inhibiting performance Bungo Regency in accommodating the aspirations of the community include external environmental factors such as social, cultural and political communities where levels of public education is still low, society has less support, and low awareness of the political community. On the internal factors of employees, affected by the lack of knowledge, experience and competence of some members of the board. At the organizations internal environmental factors such as the elements leadership council institutions judged to be disciplined and not expressly impose sanctions and disbursement procedures recess operational funds that have not been effective. Recommendations board members should be more active mensosialiasikan activity recess through print media or social media, there needs to be